EFFECT OF DEXTRIN ON WATER ACTIVITY, CRUDE FIBER, PHENOLICS, AND ORGANOLEPTIC FRUIT LEATHER GUAVA CRYSTAL-DRAGON FRUIT SKIN - Dwiloka, Bambang; Sabella, Leony Dewi; Kamil, Rafli Zulfa (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
The goal of this study was to investigate the impact of varying concentrations of dextrin in fruit leather on attributes such as crude fiber content, total phenols, and organoleptic. The study was carried out utilizing a fully randomized design, implementing four interventions that included adding dextrin at various concentrations: (P0 ) 0%, (P1 ) 1%, (P2 ) 2%, and (P3 ) 3%, each replicated five times. The test results showed aw value of 0.40 - 0.42; crude fiber 6.31 - 7.76 g/100 g; total phenols 2.61 - 3.22%, color score 1.92 - 2.68; aroma 2 - 2.8; taste 2.24 - 2.6; and texture (plastic) 2.12 - 2.68. The test results for total phenols tend to show an increase. Increasing the concentration of added dextrin reduces the crude fiber, aroma, and taste but increases the color and texture (plasticity) of fruit leather.